1973
DOI: 10.5254/1.3545009
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Black Transfer in Blends of Cis-Poly(Butadiene) with Other Elastomers

Abstract: The study of carbon black transfer by BR crystallization, elastic modulus, and electrical conductivity provides convincing evidence that carbon black does not transfer from SBR, BR, and NR—all highly unsaturated polymers— when compounds are made by conventional Banbury and mixing procedures. This agrees with the electron micrographic studies of Marsh and coworkers as well as the latest publication of Hess and coworkers. It was shown, however, that a change in the carbon black distribution occurs when a solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
18
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 0 publications
5
18
0
Order By: Relevance
“…Tg trace for BR suffers from the complication that they show exothermic cold crystallization as well as crystalline melting peaks [10,14]. This is shown in Fig.…”
Section: Compatible Elastomer Blendsmentioning
confidence: 98%
“…Tg trace for BR suffers from the complication that they show exothermic cold crystallization as well as crystalline melting peaks [10,14]. This is shown in Fig.…”
Section: Compatible Elastomer Blendsmentioning
confidence: 98%
“…Contrarily to other references from the literature [2,3,12], the increase of specific heat with temperature occurs mostly between 50°C and 100°C. Waste tires specific heat remains almost constant between 100°C and 250°C, there is only a slight increase according to temperature.…”
Section: Behaviour Below 250°cmentioning
confidence: 95%
“…The most conventional method involves the use of homopolymer, 9,10 block or graft co-polymers, [11][12][13][14][15][16] whose blocks are structurally similar or thermodynamically miscible with the heterogeneous components. Moreover, there is also early explored compatibilisation method using isotropic nanofiller such as carbon black (CB) [17][18][19] and nanosilica. 20,21 However, recent studies have reported that the compatibilisation effect of anisotropic nanofillers such as layered silicate on the immiscible polymer blend is better than the isotropic one.…”
Section: Introductionmentioning
confidence: 99%